Dynamics of Chinese Investment in Infrastructure Development in Lombok Island - Munir, Ahmad Mubarak; Husni , Valencia; Anam, Syaiful; Ayudaning D , Pamungkas (CV. Tripe Konsultan, 2025)
Chinese investment has become the subject of ongoing debates in international political economy studies. In general, scholars argue that the benefits of Chinese investment not only depend on the relationship between China and host countries but also on various state capacities. Using a case study approach, this paper aims to contribute with other scholars to understand Chinese investment patterns in third-world countries, especially Indonesia. The volume of Chinese investment in Indonesia has increased significantly in recent years. This study will focus on understanding Chinese investment patterns in infrastructure in the Mandalika Special Economic Zone (SEZ) on Lombok Island. This project received a loan through the Asian Infrastructure Investment Bank (AIIB) of 692 million dollars during 2019-2024. This paper argues that Chinese investment has contributed to complex policy-making dynamics at the national and sub-national levels.